Karakteristik Morfologi Daun pada Tumbuhan Epifit di Kawasan Bukit Sulap Kota Lubuk Linggau - Riastuti, Reny Dwi; Sari, Anggun Wulan; Rahmi, Rahmi (Institut Penelitian Matematika, Komputer, Keperawatan, Pendidikan dan Ekonomi (IPM2KPE), 2024)
This study aims to determine the morphological characteristics of leaves on epiphytic plants in the Bukit Sulap area of Lubuklinggau City. The method used is survey method, explorative and descriptive qualitative, this research was conducted by collecting data on plants, observing the morphological characteristics of the leaves and the description of the leaves. Based on the results of the study showed that the morphological characteristics of leaves on epiphytic plants in the Bukit Sulap area of Lubuklinggau City were 18 species with the morphological characteristics of epiphytic plant leaves at the base of the leaf having a dominating shape that is blunt in 8 species, the dominating leaf blade is elongated in 8 species, the dominating leaf tip is tapered in 10 species, and the dominating leaf edge is flat in 9 species. Keywords: Bukit Sulap, Leaf Morphology Characteristics, Epiphytic Plants